Assessment of Sámi food security in Finnish Lapland: climate change impacts and policy effectiveness - Heli I. Kukkurainen; Ben G. J. S. Sonneveld (International Journal of Circumpolar Health)
Accelerated climate warming in the Arctic threatens the food security of Indigenous peoples, including the Sámi in Finland. As temperatures rise nearly four times faster than the global average, ecosystems that support traditional Sámi practices, such as reindeer herding, fishing, hunting, and gathering, are increasingly disrupted. These practices are central to Sámi identity, knowledge systems, and social cohesion. However, despite these predictive narratives, the question of how these changes will affect overall food security among the Sámi remains unclear. This study aimed to: 1) investigate how climate change affects Sámi food security, 2) map concerns about anticipated impacts, and 3) assess the effectiveness of Finnish national policies. We addressed four dimensions of food security: availability, access, utilisation, and stability. Data were gathered through semi-structured interviews (N = 10), alongside a policy analysis. Findings indicate that climate change compromises the stability of the Sámi food systems and has broad implications on food security in terms of availability, accessibility, and utilisation. Current policy responses lack sufficient attention to the Sámi’s cultural-ecological ties and offer limited support for Arctic-specific adaptation. These results underscore the urgency of culturally responsive and place-based policy action to strengthen Sámi food security in a rapidly changing climate.